2019
DOI: 10.32601/ejal.651394
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Language Teachers’ Use of Social Networking Sites for Language Learning: A Quantitative Investigation

Abstract: This study examined pre-service language teachers' attitudes towards social networking site (SNS) use for language learning, their SNS practices for improving their target languages, and the relationship between them. 279 English and German language teacher candidates participated in the surveys designed for the present study. The statistical analyses of the data revealed that pre-service language teachers had positive perceptions towards SNS use for the purpose of language development and they took advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…This interpretation is in line with the qualitative findings of the present study as TV shows featuring AmE were found to be more popular among teacher candidates and exposure to popular culture and media through a variety was one of the highly cited factors for adopting an English variant. Furthermore, multiple factors such as easier access to a wide array of English varieties through the ubiquitous use of internet, teacher candidates" medium/high-level competence in web information searching skills (Atar & Bağcı, 2020) and teacher candidates" use of social media for improving their target languages (Solmaz, 2019) might provide opportunities for learners to improve their pronunciation and vocabulary knowledge autonomously. Given that "preferred input" (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is in line with the qualitative findings of the present study as TV shows featuring AmE were found to be more popular among teacher candidates and exposure to popular culture and media through a variety was one of the highly cited factors for adopting an English variant. Furthermore, multiple factors such as easier access to a wide array of English varieties through the ubiquitous use of internet, teacher candidates" medium/high-level competence in web information searching skills (Atar & Bağcı, 2020) and teacher candidates" use of social media for improving their target languages (Solmaz, 2019) might provide opportunities for learners to improve their pronunciation and vocabulary knowledge autonomously. Given that "preferred input" (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have focused on the impact of social media on the attitudes of secondary school students, looking at a range of topics including self-esteem, body image, mental health, and academic engagement. Attitudes can reflect students' opinions regarding the effectiveness, usefulness, and benefits of using social media in their language learning journey (Solmaz, 2019;Zhao et al, 2022). According to research, students' attitudes and opinions about a variety of elements of their lives, such as academic achievement, mental health, socialisation, and sexuality, can be impacted by social media (S Mahadi et al, 2023;Ojih et al, 2016).…”
Section: Social Media On Attitudes Of Secondary Studentsmentioning
confidence: 99%
“…A significant sum of studies was performed on the tertiary education level learners with 19 articles contributing to the list [30,31,35,36,[38][39][40]43,45,46,[48][49][50][51][52][53][54][55]58]. Five articles were directed towards the response from educators [33,34,42,56,57]. Meanwhile, the primary education level [29,47] secondary education level [37,44] and the general public [32,41] each have registered two articles investigating their feedback on SNS.…”
Section: N/a /mentioning
confidence: 99%